Zombie infrastructure: A legal geography of railroad monstrosity in the California desert. (August 2021) - Sizek, Julia
This paper proposes the concept of zombie infrastructure to understand the entangled histories of railroad colonialism, Indigenous dispossession, and corporate power in the California desert. I examine debates over the Cadiz project, a contemporary water project that proposes to take water from a California desert aquifer and transport it to the California coast. I argue that the life of the Cadiz project depends on Cadiz Inc.'s ability to revive the legal rights and body of a little-used railroad shortline, thus bringing back a legal infrastructure and corporate power from the late nineteenth century in the service of a new corporation. In so doing, the Cadiz project enlivens the racialized dispossession of land and labor that the railroad initially required. Routing the politics of a contemporary infrastructure project through the railroad and its octopus past, I argue, places the politics of infrastructure at the intersection of laws, monstrosity, and dispossession. Drawing on economic and legal geography, this paper proposes the concept of zombie infrastructure, a concept that builds on what activists call zombie projects in order to show the life and death of infrastructure, and reveals how contemporary capitalists enliven old infrastructures for new purposes.